Impact of random dispersion fluctuations on two-pump fiber optical parametric amplifier performances - Othman, N.; Tay, K. G.; Pakarzadeh, H.; Cholan, N. A.; M. Shah, N. S.; Talib, R. (HRPub, 2019)
The impact of random dispersion fluctuations on two-pump (2-P) fiber optical parametric amplifier (FOPA) performance in terms of parametric gain, 3-dB amplification bandwidth and saturation power is numerically investigated. The four-coupled amplitude equations which represent the parametric process in optical fiber are solved using the Runge-Kutta method. Based on the results, it was observed that the random dispersion fluctuations reduced the parametric gain, increased the saturation power and had no significant effect on 3-dB amplification bandwidth. The resulted behaviors are mainly due to the changes of phase-matching condition in optical fiber. All in all, the random dispersion fluctuations are potentially limited the 2-P FOPA performances.